Improving the Selectivity of an Osseointegrated Neural Interface: Proof of Concept For Housing Sieve Electrode Arrays in the Medullary Canal of Long Bones - Millevolte, Augusto X. T.; Dingle, Aaron M.; Ness, Jared P.; Novello, Joseph; Zeng, Weifeng; Lu, Yan; Minor, Rashea L.; Nemke, Brett; Markel, Mark D.; Suminski, Aaron J.; Williams, Justin C.; Poore, Samuel O. (Frontiers in Neuroscience, 2021)
Sieve electrodes stand poised to deliver the selectivity required for driving advanced prosthetics but are considered inherently invasive and lack the stability required for a chronic solution. This proof of concept experiment investigates the potential for the housing and engagement of a sieve electrode within the medullary canal as part of an osseointegrated neural interface (ONI) for greater selectivity towards improving prosthetic control. The working hypotheses are that A) the addition of a sieve interface to a cuff electrode housed within the medullary canal of the femur as part of an ONI would be capable of measuring efferent and afferent compound nerve action potentials through a greater number of channels; B) that signaling improves over time; and C) that stimulation at this interface generates measurable cortical somatosensory evoked potentials through a greater number of channels. The modified ONI was tested in a rabbit (n=1) amputation model over 12 weeks, comparing the sieve component to the cuff, and subsequently compared to historical data. Efferent compound nerve action potentials were successfully recorded from the sieve demonstrating physiological improvements in compound nerve action potentials between weeks 3 and 5, and somatosensory cortical responses recorded at 12 weeks postoperatively. This demonstrates that sieve electrodes can be housed and function within the medullary canal, demonstrated by improved nerve engagement and distinct cortical sensory feedback. This data presents the conceptual framework for housing more sophisticated sieve electrodes in bone as part of an ONI for improving selectivity with percutaneous connectivity towards improved prosthetic control.